Copper-N-SiO2 nanoparticles catalyst for hydrogen evolution reaction. (30th August 2019) - Khdary, Nezar Hassan; Ghanem, Mohamed A.; Abdelsalam, Mamdouh E.; Khdary, Duaa N.; Alotaibi, Nouf H.
Abstract: Herein, we report the Cu(0)-based nanoparticles film generated by in situ electrochemical reductions of Cu(II) ions modified silica exhibits a high activity and durable HER catalyst in acid solution. Copper ions were attached to silica surface using chemical modification with propyl ethylene diamine (PEDA) linker followed by treating with copper sulfate solution to form Cu(II)-PEDA/silica complex. Copper nanoparticles then were obtained by electrochemical reduction of the silica immobilized Cu(II) ions in sulfuric acid solution. The physicochemical properties of the resulted from copper nanoparticles incorporated silica were investigated and analyzed by Energy Dispersive x-ray Spectroscopy (EDS), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FT-IR), X-ray powder diffraction XRD, X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM). The electrochemical characterizations confirm that the Cu(0) nanoparticles supported on silica substrate combining both high activity and stability for hydrogen evolution reaction with overpotential(η), of 200 mV and Tafel slope of 67 mV/dec could serve as Cu-based electrocatalysts in practical applications for hydrogen production in 0.5 M of H2 SO4 solution. The catalyst exhibited respectable stability and steadily produced hydrogen at several potentials. The catalyst has the perspective to expressively lower the cost of manufacturing hydrogen fuel, thus helping to spread the use of hydrogen fuel which does not harm the environment. Graphical abstract: Image 1 Highlights: Cu-SiO2 catalyst was porduced by modifying the SiO2 surface with Cu nanoparticles. SEM, TEM, XRD and XPS confirm the presence of Cu nanoparticles and uniform distribution on SiO2 . The Cu-SiO2 catalyst showed outstanding activity for the HER in 0.5 M H2 SO4 solution. The overpotential η was -200 mV vs. SHE and the Tafel slope was 67 mV dec -1 . The catalyst showed good stability and consistently produced H2 at various potentials for 2 hours.